Solve it Algebraically? I won't dare 2

Algebra Level 2

1 1 x 1 = α \left| 1-\left| 1-\left| x-1 \right| \right| \right| =\alpha

Find the value of α \alpha for which this equation has exactly 4 distinct solutions. If the value of α \alpha is A A , then find 2 A 2A .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Apr 19, 2015

The surest way to solve this by plotting the graph of α = 1 1 x 1 \alpha = |1-|1-|x-1||| . From the graph we note that there are exactly 4 4 distinct solutions when α = 1 \alpha = 1 .

When x = { 2 α = 1 1 2 1 = 1 1 3 = 1 2 = 1 0 α = 1 1 0 1 = 1 1 1 = 1 0 = 1 2 α = 1 1 2 1 = 1 1 1 = 1 0 = 1 4 α = 1 1 4 1 = 1 1 3 = 1 2 = 1 \space x = \begin{cases} -2 & \Rightarrow \alpha = |1-|1-|-2-1||| & = |1-|1-3|| = |1-2| & = 1 \\ 0 & \Rightarrow \alpha = |1-|1-|0-1||| & = |1-|1-1|| = |1-0| & = 1 \\ 2 & \Rightarrow \alpha = |1-|1-|2-1||| & = |1-|1-1|| = |1-0| & = 1 \\ 4 & \Rightarrow \alpha = |1-|1-|4-1||| & = |1-|1-3|| = |1-2| & = 1 \end{cases}

Therefore, the answer 2 α = 2 2\alpha = \boxed{2} .

Chacha give an algebrical proof not other

Ram Sita - 3 years, 9 months ago
Sergio Melo
Nov 3, 2019

Let´s write the function step by step to get the answer:

1st: 1 x 1 1-∣x-1∣

Remember that x = ∣x∣= { x i f x < 0 x i f x 0 \begin{cases} -x\quad if\quad x<0 \\ x\quad if\quad x\ge 0 \end{cases} , so 1 x 1 = 1 1-∣x-1∣=1- { ( x 1 ) i f x < 1 x 1 i f x 1 \begin{cases} -(x-1)\quad if\quad x<1 \\ x-1\quad if\quad x\ge 1 \end{cases} . This equals to { x i f x < 1 2 x i f x 1 \begin{cases} x\quad if\quad x<1 \\ 2-x\quad if\quad x\ge 1 \end{cases}

2nd: 1 1 x 1 1-∣1-∣x-1∣∣

In this case, you take the absolute value of all the negative parts of the function above, making these parts positive, so we have to calculate when x x and 2 x 2-x are negative, x x is negative when is less than 0 0 and 2 x 2-x is negative when x > 2 x>2 .

With the absolute value, the parts of x x from -\infty to 0 0 and 2 x 2-x from 2 2 to \infty are positive. If we want to know the new functions in the positive parts, just multiply by 1 -1 both functions, so the positive parts are x -x and x 2 x-2 . This creates a new function:

1 x 1 = ∣1-∣x-1∣∣= { x i f x < 0 x i f 0 x < 1 2 x i f 1 x < 2 x 2 i f x 2 \begin{cases} -x\quad if\quad x<0 \\ x\quad if\quad 0\le x<1 \\ 2-x\quad if\quad 1\le x<2 \\ x-2\quad if\quad x\ge 2 \end{cases}

Now, since the function is negative and then added by 1 1 we have to multiply by 1 -1 each part of the function and then add the 1 to each part:

1 1 x 1 = 1-∣1-∣x-1∣∣= 1 1- { x i f x < 0 x i f 0 x < 1 2 x i f 1 x < 2 x 2 i f x 2 = \begin{cases} -x\quad if\quad x<0 \\ x\quad if\quad 0\le x<1 \\ 2-x\quad if\quad 1\le x<2 \\ x-2\quad if\quad x\ge 2 \end{cases}= 1 + 1+ { x i f x < 0 x i f 0 x < 1 x 2 i f 1 x < 2 2 x i f x 2 = \begin{cases} x\quad if\quad x<0 \\ -x\quad if\quad 0\le x<1 \\ x-2\quad if\quad 1\le x<2 \\ 2-x\quad if\quad x\ge 2 \end{cases}= { x + 1 i f x < 0 1 x i f 0 x < 1 x 1 i f 1 x < 2 3 x i f x 2 \begin{cases} x+1\quad if\quad x<0 \\ 1-x\quad if\quad 0\le x<1 \\ x-1\quad if\quad 1\le x<2 \\ 3-x\quad if\quad x\ge 2 \end{cases}

3rd: 1 1 x 1 ∣1-∣1-∣x-1∣∣

Do the same thing like the 2nd step and you´ll get that { x + 1 < 0 i f x < 1 1 x < 0 i f x > 1 x 1 < 0 i f x < 1 3 x < 0 i f x > 3 \begin{cases} x+1<0\quad if\quad x<-1 \\ 1-x<0\quad if\quad x>1 \\ x-1<0\quad if\quad x<1 \\ 3-x<0\quad if\quad x>3 \end{cases} . Note that x + 1 x+1 and 3 x 3-x have negative parts in the function of the second step, so if we take the absolute value, these parts will be positive (With the absolute value, x + 1 x+1 from -\infty to 1 -1 and 3 x 3-x from 3 3 to \infty are positive), so, the functions on these parts are ( x + 1 ) -(x+1) and x 3 x-3 .

The function is 1 1 x 1 = ∣1-∣1-∣x-1∣∣= { ( x + 1 ) i f x < 1 x + 1 i f 1 x < 0 1 x i f 0 x < 1 x 1 i f 1 x < 2 3 x i f 2 x < 3 x 3 i f x 3 \begin{cases} -(x+1)\quad if\quad x<-1 \\ x+1\quad if\quad -1\le x<0 \\ 1-x\quad if\quad 0\le x<1 \\ x-1\quad if\quad 1\le x<2 \\ 3-x\quad if\quad 2\le x<3 \\ x-3\quad if\quad x\ge 3 \end{cases}

4th: ¿The solutions?

Well, let´s analyze where we could see 4 different solutions in the equation 1 1 x 1 = α ∣1-∣1-∣x-1∣∣=α or { ( x + 1 ) i f x < 1 x + 1 i f 1 x < 0 1 x i f 0 x < 1 x 1 i f 1 x < 2 3 x i f 2 x < 3 x 3 i f x 3 = α \begin{cases} -(x+1)\quad if\quad x<-1 \\ x+1\quad if\quad -1\le x<0 \\ 1-x\quad if\quad 0\le x<1 \\ x-1\quad if\quad 1\le x<2 \\ 3-x\quad if\quad 2\le x<3 \\ x-3\quad if\quad x\ge 3 \end{cases}=α

Note that if we choose integer values x [ 1 , 3 ] x∈[-1,3] , the function is between 0 and 1, therefore, between these numbers we can choose the value of α α because if α > 1 α>1 we can find only two solutions for the equation, and we can´t choose α ( 0 , 1 ) α∈(0,1) because we can find more than 4 solutions to the equation. So if α = 0 α=0 , the equation has three solutions:

{ ( x + 1 ) i f x < 1 x + 1 i f 1 x < 0 1 x i f 0 x < 1 x 1 i f 1 x < 2 3 x i f 2 x < 3 x 3 i f x 3 = 0 { ( x + 1 ) = 0 f o r x < 1 x + 1 = 0 f o r 1 x < 0 1 x = 0 f o r 0 x < 1 x 1 = 0 f o r 1 x < 2 3 x = 0 f o r 2 x < 3 x 3 = 0 f o r x 3 x = { N 1 N 1 N 3 \begin{cases} -(x+1)\quad if\quad x<-1 \\ x+1\quad if\quad -1\le x<0 \\ 1-x\quad if\quad 0\le x<1 \\ x-1\quad if\quad 1\le x<2 \\ 3-x\quad if\quad 2\le x<3 \\ x-3\quad if\quad x\ge 3 \end{cases}=0\rightarrow \begin{cases} -(x+1)=0\quad for\quad x<-1 \\ x+1=0\quad for\quad -1\le x<0 \\ 1-x=0\quad for\quad 0\le x<1 \\ x-1=0\quad for\quad 1\le x<2 \\ 3-x=0\quad for\quad 2\le x<3 \\ x-3=0\quad for\quad x\ge 3 \end{cases}\rightarrow x=\begin{cases} N \\ -1 \\ N \\ 1 \\ N \\ 3 \end{cases}

So, the answer must be α = 1 α=1 :

{ ( x + 1 ) i f x < 1 x + 1 i f 1 x < 0 1 x i f 0 x < 1 x 1 i f 1 x < 2 3 x i f 2 x < 3 x 3 i f x 3 = 1 { ( x + 1 ) = 1 f o r x < 1 x + 1 = 1 f o r 1 x < 0 1 x = 1 f o r 0 x < 1 x 1 = 1 f o r 1 x < 2 3 x = 1 f o r 2 x < 3 x 3 = 1 f o r x 3 x = { 2 N 0 N 2 4 \begin{cases} -(x+1)\quad if\quad x<-1 \\ x+1\quad if\quad -1\le x<0 \\ 1-x\quad if\quad 0\le x<1 \\ x-1\quad if\quad 1\le x<2 \\ 3-x\quad if\quad 2\le x<3 \\ x-3\quad if\quad x\ge 3 \end{cases}=1\rightarrow \begin{cases} -(x+1)=1\quad for\quad x<-1 \\ x+1=1\quad for\quad -1\le x<0 \\ 1-x=1\quad for\quad 0\le x<1 \\ x-1=1\quad for\quad 1\le x<2 \\ 3-x=1\quad for\quad 2\le x<3 \\ x-3=1\quad for\quad x\ge 3 \end{cases}\rightarrow x=\begin{cases} -2 \\ N \\ 0 \\ N \\ 2 \\ 4 \end{cases}

The letter N in the set of solutions means that the equation doesn´t have a solution considering the interval given for each of them.

Now, since A = α A=α , 2 A = 2 2A= 2

Curtis Clement
Apr 19, 2015

There are different sets of conditions that we can apply and evaluate as follows: ( 1 ) . . . . x 2 α = 3 x \ (1).... \ x \geq\ 2 \Rightarrow\alpha = |3-x| ( 2 ) . . . . x < 2 0 ( α = 1 x ) 1 \ (2).... x < 2 \Rightarrow\ 0 \leq\ ( \alpha = | 1-|x| |) \leq\ 1 Now we will use these conditions to create conditions for alpha based on the number of real solutions that can be taken from equations (1) and (2): α = 0 x = 1 , 1 , 3 3 s o l u t i o n s \alpha = 0 \Rightarrow\ x = -1, 1 , 3 \Rightarrow\ 3 \ solutions 0 < α < 1 2 s o l u t i o n s f r o m ( 1 ) a n d 4 f r o m ( 2 ) 0 < \alpha \ < 1 \Rightarrow\ 2 \ solutions \ from (1) \ and \ 4 \ from (2) α = 1 x = 2 , 0 , 2 , 4 \alpha = 1 \Rightarrow\ x = -2, 0 , 2 , 4 α > 1 2 s o l u t i o n s f r o m ( 1 ) b u t n o n e f r o m ( 2 ) \alpha > 1 \Rightarrow\ 2 \ solutions \ from \ (1) \ but \ none \ from (2) 2 α = 2 \therefore\ 2 \alpha = 2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...